Applied physiological investigations of the structure and mechanics of the muscle-tendon complex in conjunction with associated neuromuscular performance - Pacinelli, Lauren Elizabeth (Kansas State University, 2021)
The primary objective of the investigations presented here were to examine muscle-tendon complex variables with corresponding neuromuscular performance variables. In total, three completed studies are contained within this body of work, employing noninvasive methods of ultrasound (US) and myotonometry (MYO), as well as postural stability (BAL) to explore the roles and relationships of the medial gastrocnemius (MG) and Achilles tendon (AT). Study 1 was developed to identify intra-rater reliability in measurements of MG thickness (MGT), cross-sectional area (CSA), and echo intensity (EI) using two US imaging techniques (B-mode and panoramic) compared with measurements of the same variables between each technique. Findings supported that B-mode and panoramic US imaging are reliable techniques for assessing MG MGT, CSA, and EI (ICC: 0.699-0.999; SEM%: 0.839-5.324%). Good correlations were found between B-mode and Panoramic (r = 0.791-0.892, p = 0.013-0.001), demonstrating that the two techniques might be interchangeable when assessing MGT and EI. No differences were observed between the techniques (B-mode and Panoramic) when measuring EI (p = 0.174-0.828) and MGT (p = 0.185). Study 2 was designed to explore gender differences in the free AT structure (CSA, tendon thickness [TT], and EI) utilizing B-mode and panoramic US imaging techniques. Results of this investigation demonstrated good to excellent reliability for imaging (ICC = 0.840-0.985, SEM% = 1.96-12.01%). Additionally, only tendon quality (measured as EI) was observed to be gender-dependent (p = 0.001). Study 3 was designed to explore the relationship between structural (CSA, TT, MGT, EI) and passive mechanical properties (stiffness and elasticity) of the musculotendinous junction of the MG and AT; and how those properties may be related to postural stability performance in young adult males. Findings supported that select MG structures were associated with passive mechanical properties of the AT with significantly high correlations found between MG CSA and AT elasticity (r = 0.773, p = 0.015), MGT and AT elasticity (r = 0.717, p = 0.030). Additionally, a significantly high negative correlation was observed between TT and MG EI (r = -0.770, p = 0.015). A single muscle-tendon complex property was associated with one postural stability variable, MGT and Anterior-Posterior Index (API) demonstrated a significantly high, negative relationship (r = -0.747, p = 0.021). Finally, a culminating project has been developed to identify mechanical properties (stiffness and elasticity) of the muscle-tendon complex of the knee extensors to provide a timeline of mechanical decay in conjunction with neuromuscular performance across a series of eccentric contractions, and whether age influences the onset of mechanical and neuromuscular alterations. This study will include US imaging and MYO of the rectus femoris (RF) muscle and the patellar tendon (PT) prior to, during, and after an acute bout of 10×10 maximal, voluntary eccentric contractions on an isokinetic dynamometer at a speed of 60°⸱sˉ¹. In addition to muscular structure and passive mechanics, this study will also incorporate surface electromyography (EMG) of the RF to identify and record electrical activity and neuromuscular characteristics (peak torque [PT;Nm], rate of torque development [RTD;N·m·sˉ¹], and electromechanical delay [EMD;ms]) throughout the acute eccentric contractions. Pilot data collected and analyzed following a short, acute drop jump exercise with healthy, college age males and females demonstrated a significant interaction for time*tissue, with pre-exercise RF stiffness (N/m) increasing following exercise (p = 0.027). Pilot data also demonstrated PT stiffness was greater than RF stiffness (p = 0.001).
Keywords: Achilles tendon; Medial gastrocnemius; Ultrasound; Myotonometry; Electromyography; Eccentric exercise